THE INCORPORATION OF PB INTO ZIRCON - Watson E.B.; Cherniak D.J.; Hanchar J.M.; Wark D.A.; Harrison T.M. (My University, 1997)
The incorporation of Pb into zircons grown from Pb-rich solutions was evaluated using three different approaches: (1) high-temperature growth of large crystals from Pb-silicate melts; (2) hydrothermal overplating of thin epitaxial layers on substrates of natural zircon; and (3) growth of small, homogeneously nucleated crystals from aqueous fluids. The melt-grown zircons (50–400 μm) were crystallized from PbO-SiO2-ZrO2 (±P2O5) liquid at atmospheric pressure by cooling from 1430° to 1350°C. In the P2O5 free system, despite 66 wt% PbO in the melt, these zircons contain < 1 ppm Pb, yielding an apparent crystal/melt partition coefficient (DPb) for Pb2+ of 7 × 10−7. Addition of ~ 5 wt% P2O5 to the melt results in uptake not only of P ( ~ 3400 ppm) in the zircons but also Pb (~ 1500 ppm), increasing the apparent DPb to about 10−3. Hydrothermal overplating of ZrSiO4 was carried out at 1.5 GPa in a piston-cylinder apparatus by slow cooling from 500°C or 550°C to 140°C of polished slabs of natural zircon immersed in zircon-saturated aqueous solutions containing either PbO2 or PbO + P2O5. In both cases, the resulting epitaxial layers of ZrSiO4 (∼ 60 nm thick) contain > 3 atom% Pb, with apparent zircon/fluid partition coefficients of 4.2 and 2.6, respectively, for Pb4+ and Pb2+. In contrast to the case of melt-grown zircons, available P is excluded from the aqueous epitaxial zircon, suggesting that charge balance is accomplished by H+ instead. Small (2–5 μm) zircons grown by cooling aqueous solutions (PbO + SiO2 + ZrO2 ± P2O5) from 800°C or 900°C contain ~ 0.25–0.5 atom% Pb (~ 2–4 wt% PbO), yielding apparent DPb values of ~ 0.2–0.3. Available P5+ is incorporated in a 2:1 ratio with Pb2+, suggesting a specific charge-balance mechanism: [2P5+ + Pb2+] = [2Si4+ + Zr4+]. However, Pb enters the zircon even when P is unavailable, so H+ may again play a charge-balancing role.